The second step in the construction of a stigma scale of epilepsy O segundo passo para a construção de uma escala de estigma na epilepsia - Priscila C.B. Salgado; Paula T. Fernandes; Ana Lúcia A. Noronha; Fernanda D. Barbosa; Elisabete A.P. Souza; Li M. Li (Arquivos de Neuro-Psiquiatria)
RATIONALE: The issue of stigmatization is one of the most common psychosocial problems faced by people with epilepsy. PURPOSE: A second step towards the development of a scale to measure epilepsy stigma. METHOD: We applied a closed questionnaire to 12 patients and 32 relatives from the Epilepsy Outpatient Clinic at the University Hospital of Campinas. RESULTS: The results are grouped in three main domains: medical, social and personal areas. Medical: the subjects did not know exactly what epilepsy is or how it is caused; nonetheless they know how to treat it. Social: the most important areas that people with epilepsy are discriminated are at work and social relationships. Patients also complained about their lack of freedom and limits on recreation activities. Personal Area: subjects apparently have the same feelings and thoughts about epilepsy and seizures. CONCLUSION: This study analyzed the most common aspects presented in the questionnaire to assess epilepsy stigma for the Brazilian culture which are the base to the elaboration of a stigma scale of epilepsy. INTRODUÇÃO: O estigma tem sido projetado como um dos problemas sociais mais comuns enfrentados por pessoas com epilepsia. OBJETIVO: Este estudo representa o segundo passo no desenvolvimento da escala para mensurar estigma na epilepsia. MÉTODO: O questionário foi aplicado em 12 pacientes e 32 familiares, entrevistados no Ambulatório de Epilepsia do Hospital das Clínicas, UNICAMP. RESULTADOS: Os resultados estão agrupados nas três principais áreas: médica, social e pessoal. Médica: os sujeitos mostraram não ter informação suficiente ou adequada sobre epilepsia e crises, o que não aconteceu com relação ao tratamento. Social: o trabalho e as relações sociais apareceram como os aspectos de maior discriminação na epilepsia. Os pacientes também ressaltaram a falta de liberdade e restrição de atividades de lazer como aspectos bastante prejudicados. Área pessoal: todos os sujeitos aparentemente têm os mesmos sentimentos e pensamentos sobre epilepsia e crises epilépticas. CONCLUSÃO: Este estudo analisou os aspectos mais comuns apresentados no questionário para avaliar o estigma na epilepsia na cultura brasileira, os quais serão a base da elaboração da escala de estigma na epilepsia.